Impact of online convenience on generation Z online impulsive buying behavior: The moderating role of social media celebrity - Lina, You; Hou, Deshuai; Ali, Saqib (Frontiers in Psychology, 2022)
This research aims to determine which dimensions of online convenience influence generation z consumers' cognitive and affective attitudes and online impulsive buying behavior. The moderating effect of social media celebrity is also investigated to examine the attitude-behavior gap. A total of 348 responses from Chinese users who followed digital celebrities were received using purposive sampling. Data analysis and hypothesis testing were carried out using SmartPLS, version 3 (partial least squares). The results indicated that relationship convenience, possession convenience, post possession conveniences, transaction convenience and evaluation convenience have a crucial impact on cognitive and affective attitudes. Similarly, cognitive and affective attitudes are significant and positive predictors of generation z consumers' online impulsive buying behavior. Moreover, empirical results supported the moderating role of social media celebrities that aid marketers in selecting a product endorser. The implications for marketers and policymakers are discussed based on the above research findings. Moreover, future research directions are suggested.